Epoxy polyurethane modified polyaspartic acid ester zinc-rich primer and preparation method thereof
By designing an epoxy polyurethane modified polyaspartic acid zinc-rich primer, the problems of poor salt spray resistance and slow drying performance of traditional coatings are solved, and high performance, low VOC emissions and low temperature self-drying effects are achieved. Significantly improves production efficiency and salt spray resistance.
Patent Information
- Application Number
- CN202411331980.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-17
AI Technical Summary
The problems of poor salt spray resistance of traditional asparagus polyurea coatings and slow drying performance of traditional epoxy zinc-rich primers lead to poor adhesion grade and low production efficiency in practical applications.
An epoxy polyurethane modified polyaspartic acid zinc-rich primer was designed, and its components include component A and component B. Component A contains polyaspartic acid ester resin, epoxy resin, and hydroxyacrylic resin. , zinc powder, etc., component B contains isophorone diisocyanate and hexamethylene diisocyanate homopolymer, and is dispersed and mixed uniformly through high-speed stirring to form a high-performance zinc-rich primer.
It achieves low VOC emissions, low temperature self-drying and baking, excellent physical and mechanical properties, water resistance and chemical resistance, improves production efficiency, and significantly improves salt spray resistance and dryness, reaching comparable to water-based coatings Performance level.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular is an epoxy polyurethane modified polyaspartic acid zinc-rich primer and a preparation method thereof. Background Art
[0002] Polyaspartic acid coatings have become a hot topic in the coatings research field in recent years due to their characteristics such as no baking, wet spraying, high solid content and low VOC emissions.
[0003] Polyaspartic acid ester coatings have excellent weather resistance, corrosion resistance, high hardness, low VOC emissions, and baking-free properties. However, in actual application, there is still no precedent for using it alone in heavy-duty anti-corrosion zinc-rich primers. It is more often used as a topcoat in combination with traditional epoxy anti-corrosion primers.
[0004] The invention patent with Chinese patent publication number CN116143996A discloses a polyaspartic acid ester modified epoxy resin, a marine non-toxic, environmentally friendly, wear-resistant and anti-corrosion coating containing the above resin, and a preparation method and application. The marine non-toxic, environmentally friendly, wear-resistant and anti-corrosion coating in the patent has excellent medium resistance and salt spray resistance, but has a long drying time and a poor adhesion grade. Summary of the invention
[0005] The purpose of the present invention is to solve the problems of poor salt spray resistance of traditional aspartic polyurea coatings and slow drying performance of traditional epoxy zinc-rich primers, and to provide an epoxy polyurethane modified polyaspartic acid resin-rich primer with excellent comprehensive performance and a preparation method thereof. This type of primer not only has a low VOC content, is self-drying at low temperature and does not require baking, can greatly reduce environmental protection treatment investment and production coating energy consumption, but also has excellent physical and mechanical properties, water resistance and chemical resistance, and improves actual production efficiency.
[0006] In order to achieve the above object, the present invention designs an epoxy polyurethane modified polyaspartic acid zinc-rich primer, characterized in that the ingredients include component A and component B, and the raw materials of component A include, by mass: 3-5 parts of polyaspartic acid resin a; 3 to 5 parts of polyaspartic acid resin b; 1 to 3 parts of epoxy resin; 1 to 3 parts of hydroxy acrylic resin; 3-8 parts of organic solvent; 65-80 parts of zinc powder; 1 to 6 parts of pigments and fillers; 1-2 parts of anti-rust aluminum powder; 1-2 parts of adhesion promoter; 3-5 parts of other additives; The types of compositions contained in the B component and their weight percentages are: 5-15 parts of isophorone diisocyanate; Hexamethylene diisocyanate homopolymer a 40-60 parts; Hexamethylene diisocyanate homopolymer b 20 to 40 parts; Preferably, the epoxy polyurethane modified polyaspartic acid zinc-rich primer provided by the present invention also includes other technical features: the molecular weight of the polyaspartic acid resin a is 300-900, and the NH equivalent is 270-1000; the molecular weight of the polyaspartic acid resin b is 400-1000, and the NH equivalent is 290-1100; the epoxy equivalent of the epoxy resin is 180-500; the OH content of the hydroxylated acrylic resin is 3.5-4.5%; the molecular weight of the isophorone diisocyanate is 1000-2000, and the NCO value is 4.7-7.2%; the molecular weight of the hexamethylene diisocyanate homopolymer a is 700-900, and the NCO value is 23-24%; the molecular weight of the hexamethylene diisocyanate homopolymer b is 700-900, and the NCO value is 20.5-21.5%.
[0007] Preferably, the epoxy polyurethane modified polyaspartic acid zinc-rich primer provided by the present invention also includes other technical features: the molar ratio of the sum of the NH content contained in the polyaspartic acid resin a and the polyaspartic acid resin b and the OH content of the hydroxylated acrylic resin to the sum of the NCO content contained in the isophorone diisocyanate, the hexamethylene diisocyanate homopolymer a and the hexamethylene diisocyanate homopolymer b is 1.0 to 1.2.
[0008] Preferably, the epoxy polyurethane modified polyaspartic acid zinc-rich primer provided by the present invention also includes other technical features: the color filler includes, by mass: 0.5-2 parts of mica powder; 0.5-2 parts of feldspar powder; 0.5 to 2 parts of talcum powder.
[0009] Preferably, the epoxy polyurethane modified polyaspartic acid zinc-rich primer provided by the present invention further comprises other technical features. The other additives include, by weight: 1-2 parts of dispersant; 2 to 3 parts of anti-settling agent.
[0010] Preferably, the epoxy polyurethane modified polyaspartic acid zinc-rich primer provided by the present invention also includes other technical features: the organic solvent is one or more of xylene, trimethylolbenzene, ethyl acetate, butyl acetate, and butanone.
[0011] Preferably, the epoxy polyurethane modified polyaspartic acid zinc-rich primer provided by the present invention also includes other technical features: the mass ratio of the component A to the component B is 1: (0.06-0.1).
[0012] The present invention also provides a method for preparing an epoxy polyurethane modified polyaspartic acid zinc-rich primer, comprising the following steps: S1. The polyaspartic acid ester resin a, polyaspartic acid ester resin b, epoxy resin, hydroxy acrylic resin are directly mixed, a dispersant and an anti-settling agent are added, and the mixture is stirred and dispersed at a high speed of 1500 to 2000 rpm for 20 to 40 min, a filler, zinc powder and part of an organic solvent are added in sequence, and the mixture is stirred and dispersed at a high speed of 1500 to 2000 rpm for 20 to 40 min to obtain a dispersion; S2. The dispersion and the silane coupling agent are uniformly dispersed by high-speed stirring, the metallic pigment soaked with butyl acetate is added and uniformly dispersed, the viscosity of KU is adjusted to 80 to 120 mPa·s with the remaining organic solvent, and component A is obtained after stirring; S3. The isophorone diisocyanate, hexamethylene diisocyanate homopolymer a and hexamethylene diisocyanate homopolymer b are uniformly mixed to obtain component B; S4. The components A and B are mixed evenly, and the viscosity of the organic solvent is adjusted to 60-80 s for coating 4 cups.
[0013] Compared with the existing asparagus coating technology, the present invention has the following advantages: there is no precedent for preparing zinc-rich coatings from existing asparagus products. Compared with equivalent epoxy zinc-rich heavy-duty anti-corrosion coatings, the coating of the present invention has high construction solid content, excellent drying properties, good salt spray resistance, and better acid and alkali resistance and other long-term properties, and has aging resistance comparable to that of polyurethane topcoats that epoxy zinc-rich primers do not have. DETAILED DESCRIPTION
[0014] In order to make the purpose and principle of the present invention more clear, it is further described below in conjunction with specific embodiments.
[0015] In the present invention, the polyaspartic acid ester resins a and b are selected from the combination of at least two or more of Feiyang F421, F520, F524, Covestro NH1420, and NH1520; the epoxy resin is selected from the combination of at least one or more of Nan Ya NPES-901, NPEL-128, Baling Petrochemical CYD-128, and CYD-011; the hydroxylated acrylic resin is selected from MACRYNAL® SM2810 / 75BAC, Setalux FC 2008 BA-75, and Shengjia ZJ2881A , and Sanwang's SWU3812; the dispersant is selected from a combination of one or more of BYK2013, BYK220S, BYK104S, and BYK2155; the anti-settling agent is selected from a combination of one or more of Wacker H15, Degussa R972, Core Chemical D650, Deqian BENTONE38, and Deqian BENTONE27; the adhesion promoter is selected from a combination of one or more of Maitu MP200, Silicon Union Chemical USi-O2301, Jianghan New Materials JH-OP191, and Shenzhu SN-7560; the hexamethylene diisocyanate homopolymers a and b are selected from a combination of at least two or more of Covestro N3900, N3600, Asahi Kasei TLA100, Wanhua HT300, and Feiyang GB951-100; the isophorone diisocyanate is selected from a combination of one or more of Feiyang GB905A-85 and GB926-85.
[0016] The specific steps of the embodiment are as follows: Case 1 An epoxy polyurethane modified polyaspartic acid zinc-rich primer, the components are selected and the weight ratio is as follows: Component A 4 parts of polyaspartic acid resin a; 4 parts of polyaspartic acid resin b; 1 part epoxy resin; 1 part of hydroxy acrylic resin; 2 parts of anti-rust aluminum powder; Zinc powder 78 parts; 1 part mica powder; 1 part of feldspar powder; 1 part talcum powder; 3 parts of butyl acetate; 4 parts of other additives; Among them, other additives are fumed silica, organic bentonite, BYK2013, BYK220S; Component B 5 parts of isophorone diisocyanate; 60 parts of hexamethylene diisocyanate homopolymer a; 35 parts of hexamethylene diisocyanate homopolymer b; The molar ratio of OH contained in the resin of component A to NCO contained in the isocyanate in component B is 1.05; The specific preparation steps are as follows: (1) directly mixing polyaspartic acid ester resin a, polyaspartic acid ester resin b, epoxy resin, and hydroxy acrylic resin, adding dispersant and anti-settling agent, stirring and dispersing at a speed of 1500 to 2000 rpm for 20 to 40 minutes, adding filler, zinc powder, and part of organic solvent in turn, stirring and dispersing at a speed of 1500 to 2000 rpm for 20 to 40 minutes, and obtaining a dispersion; (2) The dispersion liquid and the silane coupling agent are uniformly dispersed by high-speed stirring, and the anti-rust aluminum powder soaked in butyl acetate is added and dispersed evenly, and the KU viscosity is adjusted to 80-120 mPa·s with the remaining organic solvent, and component A is obtained after stirring evenly; (3) isophorone diisocyanate, hexamethylene diisocyanate homopolymer a and hexamethylene diisocyanate homopolymer b are uniformly mixed to obtain component B; (4) Mix component A and component B in a mass ratio of 1:0.061 and stir evenly. Adjust the viscosity of the organic solvent to 60 to 80 seconds for coating 4 cups.
[0017] The above examples are subjected to various performance tests, and the test results (all resistance properties are tested on rough substrate boards) are shown in Table 1: Table 1 Case 2 An epoxy polyurethane modified polyaspartic acid zinc-rich primer, the components are selected and the weight ratio is as follows: Component A 4 parts of polyaspartic acid resin a; 5 parts of polyaspartic acid resin b; 1 part epoxy resin; 2 parts of hydroxy acrylic resin; 2 parts of anti-rust aluminum powder; 75 parts of zinc powder; 1 part mica powder; 1 part of feldspar powder; 2 parts of talcum powder; 3 parts of butyl acetate; 4 parts of other additives; Among them, other additives are fumed silica, organic bentonite, BYK2013, BYK220S; Component B 5 parts of isophorone diisocyanate; 55 parts of hexamethylene diisocyanate homopolymer a; 40 parts of hexamethylene dimer homopolymer b; The molar ratio of NH and OH contained in the resin of component A to NCO contained in the isocyanate in component B is 1.05; The specific preparation steps are as follows: (1) directly mixing polyaspartic acid ester resin a, polyaspartic acid ester resin b, epoxy resin, and hydroxy acrylic resin, adding dispersant and anti-settling agent, stirring and dispersing at a speed of 1500 to 2000 rpm for 20 to 40 minutes, adding filler, zinc powder, and part of organic solvent in turn, stirring and dispersing at a speed of 1500 to 2000 rpm for 20 to 40 minutes, and obtaining a dispersion; (2) The dispersion liquid and the silane coupling agent are uniformly dispersed by high-speed stirring, and the anti-rust aluminum powder soaked in butyl acetate is added and dispersed evenly, and the KU viscosity is adjusted to 80-120 mPa·s with the remaining organic solvent, and component A is obtained after stirring evenly; (3) isophorone diisocyanate, hexamethylene diisocyanate homopolymer a and hexamethylene diisocyanate homopolymer b are uniformly mixed to obtain component B; (4) Mix component A and component B in a mass ratio of 1:0.067 and stir evenly. Adjust the viscosity of the organic solvent to 60 to 80 seconds for coating 4 cups.
[0018] The above examples are subjected to various performance tests, and the test results (all resistance properties are tested on rough substrate boards) are shown in Table 2: Table 2 Inspection items Detection Methods Example 1 Dry film thickness (um) GB / T13452.2-2008 70-80 Press dry GB / T1728 25min VOC (g / L) GB / T24409-2020 Appendix A 163g / L Applicable period (h) GB / T 31416-2015 >2h Mass solid content% GB / T1725 93.8% Adhesion GB / T 9286 Level 0 Alkali resistance GB / T 9274 No bubbles, no wrinkles Neutral salt spray resistance GB / T 1771-2007 1560hr scratch width of one side rust ≤ 2mm, no blistering, no rust, no peeling on the board surface Case 3 An epoxy polyurethane modified polyaspartic acid zinc-rich primer, the components are selected and the weight ratio is as follows: Component A 3.5 parts of polyaspartic acid resin a, 5 parts of polyaspartic acid resin b, 1.5 parts of epoxy resin, 1.5 parts of hydroxy acrylic resin, 1 part of anti-rust aluminum powder, 74 parts of zinc powder, 2 parts of mica powder, 1.5 parts of feldspar powder, 2 parts of talcum powder.
[0019] 4 parts of butyl acetate, Other additives 3 parts, Among them, other additives are fumed silica, organic bentonite, BYK2013, BYK220S; Component B 5 parts of isophorone diisocyanate, 55 parts of hexamethylene diisocyanate homopolymer a, 40 parts of hexamethylene diisocyanate homopolymer b; The molar ratio of OH contained in the resin of component A to NCO contained in the isocyanate in component B is 1.05; The specific preparation steps are as follows: (1) directly mixing polyaspartic acid ester resin a, polyaspartic acid ester resin b, epoxy resin, and hydroxy acrylic resin, adding dispersant and anti-settling agent, stirring and dispersing at a speed of 1500 to 2000 rpm for 20 to 40 minutes, adding filler, zinc powder, and part of organic solvent in turn, stirring and dispersing at a speed of 1500 to 2000 rpm for 20 to 40 minutes, and obtaining a dispersion; (2) The dispersion liquid and the silane coupling agent are uniformly dispersed by high-speed stirring, and the anti-rust aluminum powder soaked in butyl acetate is added and dispersed evenly, and the KU viscosity is adjusted to 80-120 mPa·s with the remaining organic solvent, and component A is obtained after stirring evenly; (3) isophorone diisocyanate, hexamethylene diisocyanate homopolymer a and hexamethylene diisocyanate homopolymer b are uniformly mixed to obtain component B; (4) Mix component A and component B in a mass ratio of 1:0.073 and stir evenly. Adjust the viscosity of the organic solvent to 60 to 80 seconds for coating 4 cups.
[0020] The above examples are subjected to various performance tests, and the test results (all resistance properties are tested on rough substrate boards) are shown in Table 3: Table 3 Inspection items Detection Methods Example 1 Dry film thickness (um) GB / T13452.2-2008 70-80 Press dry GB / T1728 23min VOC (g / L) GB / T24409-2020 Appendix A 168g / L Applicable period (h) GB / T 31416-2015 >2h Mass solid content% GB / T1725 92.8% Adhesion GB / T 9286 Level 0 Alkali resistance GB / T 9274 No bubbles, no wrinkles Neutral salt spray resistance GB / T 1771-2007 1560hr scratch width of one side rust ≤ 2mm, no blistering, no rust, no peeling on the board surface It can be seen from Tables 1, 2 and 3 that the epoxy polyurethane modified polyaspartic acid zinc-rich primer prepared in this embodiment has low VOC emissions comparable to water-based primers, and has drying properties that conventional epoxy zinc-rich primers do not have, which greatly improves the efficiency of the application process, and has chemical resistance that is not lower than the existing epoxy system zinc-rich products, and neutral salt spray resistance that is not lower than or even higher than the existing epoxy zinc-rich primer products, and neutral salt spray resistance is much higher than the existing polyurea products.
[0021] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent substitutions or changes according to the technical solutions and novel concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. An epoxy polyurethane modified polyaspartic acid zinc-rich primer, characterized in that: The composition includes component A and component B, and the raw materials of component A include, by weight: 3-5 parts of polyaspartic acid resin a; 3 to 5 parts of polyaspartic acid resin b; 1 to 3 parts of epoxy resin; 1 to 3 parts of hydroxy acrylic resin; 3-8 parts of organic solvent; 65-80 parts of zinc powder; 1 to 6 parts of pigments and fillers; 1-2 parts of anti-rust aluminum powder; 1~2 parts of adhesion promoter; 3-5 parts of other additives; The types of compositions contained in the B component and their weight percentages are: 5-15 parts of isophorone diisocyanate; Hexamethylene diisocyanate homopolymer a 40-60 parts; Hexamethylene diisocyanate homopolymer b: 20 to 40 parts.
2. The epoxy polyurethane modified polyaspartic acid zinc-rich primer according to claim 1, characterized in that: The molecular weight of the polyaspartic acid ester resin a is 300-900, and the NH equivalent is 270-1000; the molecular weight of the polyaspartic acid ester resin b is 400-1000, and the NH equivalent is 290-1100; the epoxy equivalent of the epoxy resin is 180-500; the OH content of the hydroxylated acrylic resin is 3.5-4.5%; the molecular weight of the isophorone diisocyanate is 1000-2000, and the NCO value is 4.7-7.2%; the molecular weight of the hexamethylene diisocyanate homopolymer a is 700-900, and the NCO value is 23-24%; the molecular weight of the hexamethylene diisocyanate homopolymer b is 700-900, and the NCO value is 20.5-21.5%.
3. The epoxy polyurethane modified polyaspartic acid zinc-rich primer according to claim 1, characterized in that: The molar ratio of the sum of the NH content in the polyaspartic acid ester resin a and the polyaspartic acid ester resin b and the OH content in the hydroxy acrylic resin to the sum of the NCO content in the isophorone diisocyanate, the hexamethylene diisocyanate homopolymer a and the hexamethylene diisocyanate homopolymer b is 1.0 to 1.
2.
4. The epoxy polyurethane modified polyaspartic acid zinc-rich primer according to claim 1, characterized in that: The pigments and fillers include, by mass: 0.5-2 parts of mica powder; 0.5-2 parts of feldspar powder; 0.5 to 2 parts of talcum powder.
5. The epoxy polyurethane modified polyaspartic acid zinc-rich primer according to claim 1, characterized in that: The other additives include by weight: 1-2 parts of dispersant; 2 to 3 parts of anti-settling agent.
6. The epoxy polyurethane modified polyaspartic acid rich primer according to claim 1, characterized in that: The organic solvent is one or more of xylene, trimethylbenzene, ethyl acetate, butyl acetate and butanone.
7. The epoxy polyurethane modified polyaspartic acid zinc-rich primer according to claim 1, characterized in that: The mass ratio of the component A to the component B is 1: (0.06-0.1).
8. A method for preparing the epoxy polyurethane modified polyaspartic acid zinc-rich primer as claimed in claim 1, characterized in that: The following steps are involved: S1. The polyaspartic acid resin a, polyaspartic acid resin b, epoxy resin, hydroxy acrylic resin are directly mixed, a dispersant and an anti-settling agent are added and stirred and dispersed, and then fillers, zinc powder and part of the organic solvent are added successively and stirred and dispersed to obtain a dispersion; S2. The dispersion and the silane coupling agent are uniformly dispersed by high-speed stirring, the metallic pigment soaked with butyl acetate is added and uniformly dispersed, the viscosity of KU is adjusted to 80 to 120 mPa·s with the remaining organic solvent, and component A is obtained after stirring; S3. The isophorone diisocyanate, hexamethylene diisocyanate homopolymer a and hexamethylene diisocyanate homopolymer b are uniformly mixed to obtain component B; S4. The component A and the component B are mixed evenly, and the viscosity of the organic solvent is adjusted to 60 to 80 seconds for coating a 4-cup coating.
Citation Information
Patent Citations
Flexible heavy-duty anticorrosive polyurea coating
CN106854428A
Polyurea coating and preparation method thereof
CN113045971A
Wind power blade coating and preparation method thereof
CN113122120A
Thin coating type high-corrosion-resistance high-solid-content polyaspartic acid ester primer and preparation method thereof
CN116376410A
